Novel oxidative cutting graphene oxide to graphene quantum dots for electrochemical sensing application. (September 2016) - Wen, Jiawei; Li, Mingjie; Xiao, Jiadong; Liu, Chenming; Li, Zehui; Xie, Yongbing; Ning, Pengge; Cao, Hongbin; Zhang, Yi
Graphical abstract: Highlights: A novel, mass-scale and environmental-friendly method for synthesis of high-purity GQDs was proposed without any post-treatment. The as-generated GQDs exhibited excellent photoluminescence property with uniform lateral dimension of 4–10 nm. The as-generated GQDs exhibited superior performance as electrode materials for electrochemically detection of Cu 2+ as low as 3 × 10 −10 M. Abstract: Here, for the first time, an integrated O3 /H2 O2 /ultrasound process was proposed for the synthesis of graphene quantum dots (GQDs) with uniform lateral dimension of 4–10 nm. The hydroxyl radicals dominated cleavage effect was mainly responsible for tailoring graphene sheets into quantum dots. The resultant GQDs exhibited superior performance as electrode materials for electrochemically monitoring trace Cu 2+ with a detection limit as low as 3 × 10 −10 M.